Masyarakat Adat versus Korporasi: Konflik Sosial Rencana Pembangunan Pabrik Semen di Kabupaten Pati Jawa Tengah Periode 2013-2016 - Suharko Suharko (Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Social confilct between indigenous community of Sedulur Sikep and PT SMS has arisen as a consequence of utilization of karst for cement plant in District of Pati, Central Java since 2010. Using secondary data collected from off line and on line media, and applying Wehr's model of conflict mapping, the article aims to map the conflict. For the corporation, karst can be mined and has a high economic value. For Sedulur Sikep, karst must be concerved because it covers water reservoir that is vital for its agricultural livelihood. From 2010 to 2014, while Sedulur Sikep continuesly rejected the establishment of the plant, PT SMS had completed environmental impact analysis. After Head of Pati district launched an environmental licence for PT SMS in the end of 2014, the two parties of conflict had been head to head in two levels of the administrative courts (PTUN Semarang and PTTUN Surabaya). The verdicts of court are not able to end the conflict yet. Opportunity to solve the conflict will depend on the results of strategic environmental analysis (KLHS) that was decided by the President as a reference for parties who plan to mine karst in mountain of Kendeng Utara, Central Java